2015
DOI: 10.3390/md13074197
|View full text |Cite
|
Sign up to set email alerts
|

Red Algae (Rhodophyta) from the Coast of Madagascar: Preliminary Bioactivity Studies and Isolation of Natural Products

Abstract: Several species of red algae (Rhodophyta) from the coastal regions of Madagascar have been investigated for their natural products. The most abundant compound was cholesterol (5) in combination with a series of oxidized congeners. The brominated indoles 1–3 along with the sesquiterpene debilone (4) have been isolated from Laurencia complanata. For the first time, debilone (4) has been obtained from a marine plant. From the methanol extract of Calloseris sp., we have achieved the second isolation of the unusual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 45 publications
3
35
0
Order By: Relevance
“…When the indoles 952, 969, and 971 were tested against antibiotic-resistant clinical bacteria, only 952 was proven active [432]. The antimicrobial activity of a Laurencia complanata extract containing the bromoindoles 952, 969, and 971 and the aristolane debilone (456) could be, at least to some extent, attributed to the presence of compound 952 [433]. The antibacterial activity of 4,5,6-tribromo-2-methylsulfinylindole (964), along with a series of other previously reported related compounds has been examined [801].…”
Section: Antibacterial and Antifungal Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…When the indoles 952, 969, and 971 were tested against antibiotic-resistant clinical bacteria, only 952 was proven active [432]. The antimicrobial activity of a Laurencia complanata extract containing the bromoindoles 952, 969, and 971 and the aristolane debilone (456) could be, at least to some extent, attributed to the presence of compound 952 [433]. The antibacterial activity of 4,5,6-tribromo-2-methylsulfinylindole (964), along with a series of other previously reported related compounds has been examined [801].…”
Section: Antibacterial and Antifungal Activitymentioning
confidence: 99%
“…The acetogenins panacene (746) [78], brasilenyne (891), (Z)-dihydrorhodophytin (810) and (Z)-isodihydrorhodophytin (817) [221], as well as the sesquiterpenes brasudol (432) and isobrasudol (433) [419] exhibited variable levels of inhibition of fish feeding activity. Pacifigorgiol (485), a highly rearranged sesquiterpene, exhibited toxicity towards the reef-dwelling fish Eupomacentrus leucostictus [900].…”
Section: Antifeedant Activity and Toxicity To Marine Organismsmentioning
confidence: 99%
“…When the indoles 952, 969, and 971 were tested against antibiotic-resistant clinical bacteria, only 952 was proven active [432]. The antimicrobial activity of a Laurencia complanata extract containing the bromoindoles 952, 969, and 971 and the aristolane debilone (456) could be, at least to some extent, attributed to the presence of compound 952 [433]. The antibacterial activity of 4,5,6-tribromo-2-methylsulfinylindole (964), along with a series of other previously reported related compounds has been examined [801].…”
Section: Antibacterial and Antifungal Activitymentioning
confidence: 99%
“…The acetogenins panacene (746) [78], brasilenyne (891), (Z)-dihydrorhodophytin (810) and (Z)-isodihydrorhodophytin (817) [221], as well as the sesquiterpenes brasudol (432) and isobrasudol (433) [419] exhibited variable levels of inhibition of fish feeding activity. Pacifigorgiol (485), a highly rearranged sesquiterpene, exhibited toxicity towards the reef-dwelling fish Eupomacentrus leucostictus [900].…”
Section: Antifeedant Activity and Toxicity To Marine Organismsmentioning
confidence: 99%
“…Previous report has shown that about 9% of biologically active compounds from marine organisms are present in algae. 2 Many species of algae thrive in extreme environmental conditions and have developed survival mechanisms, which lead to the release of unique primary and secondary metabolites that are absent in terrestrial plants. 3 Also, up to 50% of drugs approved by the Food and Drug Administration (FDA) in the United States consists of secondary metabolites derived from marine organisms and their synthetic analogs 4 and about 30 % of these metabolites are obtained from algae.…”
Section: Introductionmentioning
confidence: 99%